Cybersecurity for beginners - Meeuwisse, Raef (Cyber Simplicity, 2017)
This book provides an easy insight into the essentials of cybersecurity, even if you have a non-technical background. You may be a business person keen to understand this important subject area or an information security specialist looking to update your knowledge. 'The world has changed more in the past 10 years than in any 10 year period in human history... Technology is no longer a peripheral servant, it shapes our daily lives. Companies that can use technology wisely and well are booming, companies that make bad or no technology choices collapse and disappear. The cloud, smart devices and the ability to connect almost any object to the internet are an essential landscape to use but are also fraught with new risks and dangers of a magnitude never seen before